THE INFLUENCING FACTORS ON EMPLOYEE WORK SATISFACTION AT PT.INDOMACO ADI PRIMA BENGKULU : THE INFLUENCING FACTORS ON EMPLOYEE WORK SATISFACTION AT PT.INDOMACO ADI PRIMA BENGKULU - Sri Handayani; Andriyani Prawitasari (Universitas Muhammadiyah Bengkulu, 2023)
This study aims to determine the factors that give the biggest influence on employee job satisfaction at PT.Indomarco Adi Prima in Bengkulu City. It is used a rating scale as the analytical method. The result showed that most of the respondent's answers with total 321 choose an agree criteria for four factors that influencing employee job satisfication such as ; mentally challenging work, appropriate reward factors,supportive work and supportive colleague factors. Those factors are found to be significant in influencing the employee job satisfaction of PT.Indomarco Adi Prima in Bengkulu city. The highest factor that gave the biggest influence on employee job satisfaction in PT.Indomarco Adi Prima Bengkulu is a work factor that is mentally challenging, with an average score of answers of 329 with agreed criteria. Meanwhile, the lowest factor influencing employee job satisfaction in carrying out work at PT.Indomarco Adi Prima Bengkulu is the award that corresponds to the average answer score of 300 from the perceptions of respondents with agreed criteria.